Rancang Bangun Mesin Pengayak Terasi Bubuk Guna Meningkatkan Output Produksi dengan Pendekatan Antropometri - Febyyanti , Nurul; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Increased consumer demand makes UMKM H.J Irin experience obstacles that are quite influential on production process activities. In this study, an ergonomic sieving machine design with anthropometric methods was carried out with the aim of helping the sieving process to be faster and increase productivity. Anthropometry is a method used to determine the size that is in accordance with anthropometric data obtained from the measurement of the worker's body. This research uses the time study method by making direct observations recording normal time and standard time. From the results of data processing that has been carried out from the anthropometric results of workers, the dimensions of the machine are obtained at a machine height of 82 cm, a machine width of 50 cm, and a machine reach of 67 cm. The increase that occurs in the sieving process is obtained an increase in productivity that occurs by 1.40%, with details of the productivity of manual sieving tools of 14% and after the design of the machine as much as 15.40%.